Эффекты перколяции в композитах сверхпроводник-половинный металл - Кононенко, В.В.; Таренков, В.Ю.; Дьяченко, А.И.; Варюхин, В.Н. (Физика и техника высоких давлений, 2013)
В широком температурном интервале исследованы транспортные характеристики композита сверхпроводника MgB₂ и нанопорошка манганита La₀.₇Sr₀.₃MnO₃ (LSMO) с различным объемным содержанием магнитной примеси. Обнаружено, что уже 20% примеси манганита нарушают перколяционные пути диборида магния. Это приводит к значительному уширению сверхпроводящего перехода MgB₂ и образованию сетки слабосвязанных контактов через ферромагнитные включения. Полученный результат показывает возможность реализации на границе сверхпроводник–манганит спин-активированной поверхности, допускающей свободное прохождение куперовских пар с s-волновой симметрией параметра порядка через ферромагнетик со 100%-ной спиновой поляризацией носителей. У широкому температурному інтервалі досліджено транспортні характеристики композиту надпровідника MgB₂ і нанопорошка манганіту La₀.₇Sr₀.₃MnO₃ (LSMO) з різним об’ємним вмістом магнітної домішки. Знайдено, що вже 20% домішки манганітів порушують перколяційні шляхи деборіду магнію, що призводить до значного уширення надпровідного переходу MgB₂ й утворення сітки слабопов’язаних контактів через феромагнітні включення. Отриманий результат показує можливість реалізації на кордоні надпровідник–манганіт спін-активованої поверхні, яка допускає вільне проходження куперовських пар з s-хвильовою симетрією параметра порядку через феромагнетик зі 100%-ною спіновою поляризацією носіїв. Transport characteristics of the composite of the MgB₂ superconductor and nanopowder of manganite La₀.₇Sr₀.₃MnO₃ (LSMO) with varied content of magnetic impurity are investigated. A differential peculiarityof the composite is substantially varied granule size of MgB₂ (d = 5−8 μm) and LSMO (d = 8−10 μm). It is demonstrated that mixing and high pressure at the sample formation result in effect of coating of larger grains of magnesium diboride by manganite nanoparticles. This fact is accompanied by breakdown of percolation routes of magnesium diboride even at the concentrations below 20% of magnetic doping. As a result, superconducting transition of MgB₂ becomes substantially wider and a grid of weakly-bound contacts through ferromagnetic inclusions is formed. The form of current-voltage characteristics indicates weakly bound character of the tested structure, too. The obtained result makes possible realization of spin-active surface at the interface of superconductor and manganite. In this case, Cooper’s pairs with s-wave symmetry of the order parameter can be transformed into pairs with p-symmetry where the spins of both electrons are directed along the quantization axis. These pairs will have a clear passage through the half-metal.